What Made Them Successful. Issue 3 (March 2015) - Rudnicki, Pamela A.; Liang, Fan; Prince, Noah H.; Lipsitz, Stuart; May, James W.; Guo, Lifei
<x xml:space="preserve">Abstract</x> Background: The purpose of this study is to assess which personal characteristics and external factors are important contributors to eventual success. Methods: The authors distributed a survey to all members of the American Association of Plastic Surgeons and asked responders to rate the importance of 10 preselected qualities in contributing to their personal success. Survey outcomes were analyzed across different demographic groups. Results: Of the 580 American Association of Plastic Surgeons members who were surveyed, 295 returned completed surveys. Overall analysis indicates that hard work, compassion, and manual dexterity are the 3 most important attributes. Many significant differences are observed across demographic groups, indicating potential biases among the survey responders. Notably, we find that male surgeons attribute mentorship to success much more so than female surgeons (Column Trend Exact [CTE], P = 0.021), whereas female surgeons are more likely to attribute their success to hard work (CTE, P = 0.023). Similarly, those who have been program directors credit their success to mentoring more so than nonprogram directors (CTE, P < 0.00001). The authors also found that senior surgeons, as measured by years in practice, place greater emphasis on mentoring and career opportunities than younger surgeons (Mantel-Haenszel Trend, P = 0.003 and 0.0009, respectively). It is also interesting to note that individual talent qualities tend to be favored by more senior surgeons and those with more distant ties to academia. Conclusion: The authors believe that recognizing the relative importance of such factors, and their associated biases, is essential for the process of selecting and developing future successful plastic surgeons.